2024
DOI: 10.1002/wps.21156
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder: a comprehensive review of diagnosis and clinical presentation, etiology, treatment, and current controversies

Falk Leichsenring,
Peter Fonagy,
Nikolas Heim
et al.

Abstract: Borderline personality disorder (BPD) was introduced in the DSM‐III in 1980. From the DSM‐III to the DSM‐5, no major changes have occurred in its defining criteria. The disorder is characterized by instability of self‐image, interpersonal relationships and affects. Further symptoms include impulsivity, intense anger, feelings of emptiness, strong abandonment fears, suicidal or self‐mutilation behavior, and transient stress‐related paranoid ideation or severe dissociative symptoms. There is evidence that BPD ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 266 publications
(408 reference statements)
0
6
0
Order By: Relevance
“…Moreover, SB-APP was more effective than the control group in relation to the following symptoms: identity problematics, dissociative symptoms, paranoia, affective instability, disturbed relationships, and abandonment issues. The follow-up was administered after 6 and 12 months, and showed that the positive effects were maintained, moreover suicidal attempts, feelings of loss, and symptoms severity were reduced (Amianto et al, 2011; Leichsenring et al, 2024; Storebø et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, SB-APP was more effective than the control group in relation to the following symptoms: identity problematics, dissociative symptoms, paranoia, affective instability, disturbed relationships, and abandonment issues. The follow-up was administered after 6 and 12 months, and showed that the positive effects were maintained, moreover suicidal attempts, feelings of loss, and symptoms severity were reduced (Amianto et al, 2011; Leichsenring et al, 2024; Storebø et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Borderline Personality Disorder (BPD) is a prevalent and complex mental health condition characterized by pervasive instability in emotional regulation, interpersonal relationships, self-image, and impulse control. Treatment for BPD has shown to be effective [ 1 – 3 ]. Informing patients about their illness is not only an ethical responsibility for healthcare professionals but also a crucial step in the management of the condition [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that individuals with BPD often receive insufficient information about their diagnosis, leading to experiences of stigma and misunderstanding [ 8 12 ]. Despite these challenges, advancements have been made in the diagnostic process, and clinical practice guidelines are now in place to guide professionals [ 3 ]. These guidelines recommend providing patients and their families with detailed information about the disorder, including its characteristics, etiological hypotheses, prognosis, and therapeutic options [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 5 ) followed 290 adult BPD inpatients over a 24-year period and found that 5.9% of borderline patients died by suicide, indicating an increased risk of premature death among individuals with BPD. Despite the significant risk associated with BPD, it remains a challenging disorder both in terms of diagnosis and treatment ( 6 ). There is ongoing controversy regarding its conceptualization, with debate over whether it should be viewed as a specific personality disorder or as a level of impairment in general personality functioning ( 7 ).…”
Section: Introductionmentioning
confidence: 99%